Familial Relations of Russian Naval Officer N.V. Kopytov: based on Epistolary Sources of 1866-1897 - Irina V. Sinova (RUDN Journal of Russian History, 2023)
The author in their work analyzes familial relations, gender roles and gender equality issues based on Vice Admiral N.V. Kopytov’s letters to his wife, letters currently being stored in his personal fund stored at the Russian State Archive of Navy. The novelty of the scientific usefulness of the letters is determined by their use as a source base for further historical analysis. The introduction of N.V. Kopytov’s personal letters into scientific use for the first time has allowed the authors and further researchers to obtain information to analyze a wide range of issues: including interpersonal communications, gender relations, everyday life, and professional activities. In addition, this research has allowed the analysis of the influence of peculiarities of mentality, class affiliation, financial situation on the character and main priorities of relationships in N.V. Kopytov’s family. Recent research interest in personal letters as historical sources of private origin and the epistolary genre is currently associated with the ability to identify common and specific features of intra-family communications of people of a certain social stratum and social status, in this particular case, the noble family of the Vice-Admiral of Navy. The study of the letters allows us to conclude that the Kopytov family was not typical of Russian society and was more of an equal partnership, despite the prevailing gender inequality enshrined in the legislation and in the mentality of the population of time. The authors have examined the causes of family relations which were considered progressive for the period under consideration, based on the equal division of gender roles and the position of spouses in joint decision-making.